Scandal and democracy : media politics in Indonesia - McCoy, Mary E., 1968- (Southeast Asia Program Publications, an imprint of Cornell University Press, 2019)
"Focuses on the under-theorized role of the media to explain why some democratic transitions succeed and others founder and why some lead to consolidation while others either fail outright or settle into a state of pseudo-democracy that often masks an atavistic authoritarianism"--